A smallness condition ensuring boundedness in a two-dimensional chemotaxis-Navier-Stokes system involving Dirichlet boundary conditions for the signal. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Acta Mathematica Sinica (English Series))

Global mass-preserving solutions to a chemotaxis-fluid model involving Dirichlet boundary conditions for the signal. - Wang, Yulan; Winkler, Michael; Xiang, Zhaoyin (Analysis and Applications)

Developmental Paths of Pointing for Various Motives in Infants with and without Language Delay - Rohlfing, Katharina J.; Lüke, Carina; Liszkowski, Ulf; Ritterfeld, Ute; Grimminger, Angela (International Journal of Environmental Research and Public Health)
Pointing is one of the first conventional means of communication and infants have various motives for engaging in it such as imperative, declarative, or informative. Little is known about the developmental paths of producing and understanding these different motives. In our longitudinal study (N = 58) during the second year of life, we experimentally elicited infants’ pointing production and comprehension in various settings and under pragmatically valid conditions. We followed two steps in our analyses and assessed the occurrence of canonical index-finger pointing for different motives and the engagement in an ongoing interaction in pursuit of a joint goal revealed by frequency and multimodal utterances. For understanding the developmental paths, we compared two groups: typically developing infants (TD) and infants who have been assessed as having delayed language development (LD). Results showed that the developmental paths differed according to the various motives. When comparing the two groups, for all motives, LD infants produced index-finger pointing 2 months later than TD infants. For the engagement, although the pattern was less consistent across settings, the frequency of pointing was comparable in both groups, but infants with LD used less canonical forms of pointing and made fewer multimodal contributions than TD children.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Expression of CXCR4 on CD4+ T cells predicts body composition parameters in female adolescents with anorexia nervosa. - Freff, J; Bröker, L; Leite Dantas, R; Schwarte, K; Bühlmeier, J; Kraft, I; Hinney, A; Buhlmann, U; Arolt, V; Dannlowski, U; Romer, G; Baune, BT; et al. (Front Psychiatry)

Participative human-factor evaluation in the context of digital work (re-)design - Schumacher, Jan-Philip; Depenbusch, Sarah; Straatmann, Tammo; Bender, Elena; Schaper, Niclas; Hamborg, Kai-Christoph (Work)
BACKGROUND: Challenged by digital transformation, organizations increasingly integrate information and communication technologies into work designs. Often focal points of such digital reengineering initiatives are technical and economic aspects. Yet, as integration of new technologies affects how employee work and interact, there is a need to evaluate human-centered criteria (human-factor evaluation), optimally by involving employees as situational experts. OBJECTIVE: The present study develops an integrative and persona-based evaluation approach of human-centered criteria for application in participative digital (re-)design of work to support the joint optimization of the technical and social system. METHODS: Drawing on methods from usability evaluation, a persona-based approach is developed to facilitate comprehension and application of human-centered evaluation by employees. To that end, human-centered criteria from existing evaluation models are systemized with specific reference to digital transformation of work processes. The developed approach is tested in pilot runs of three German small and medium-sized enterprises (SMEs). RESULTS: The initial overview shows a divergence of specific human-centered criteria at the detailed level. Simultaneously, a high convergence is found for overarching dimensions and categories. The Integrative Socio-Digital Evaluation Model (ISDEM) is developed to balance complexity and abstraction of criteria. The derived persona-based approach (persISDEM) shows a good applicability in the pilot runs. CONCLUSIONS: The present study provides an amendment to existing work design approaches with an emphasis on employee participation, enabling organizations to foster employees’ comprehension and motivation to engage in evaluations of digital (re-)design of work and to create motivating and healthy jobs for successful digital transformation.
Keywords: Public Health; Environmental and Occupational Health; Rehabilitation

Multiplikative Beziehungen erkennen und nutzen – Initiierung von Lernprozessen durch Entdeckervideos - Häsel-Weide, Uta; Wienhues, Inga; Kordes, L. (Digitale Medien und Heterogenität – Chancen und Herausforderungen für die Mathematikdidaktik)

Qualitätssicherung im bildungswissenschaftlichen Studium – methodologische Überlegungen. - Seifert, Andreas; Watson, Christina (DGPs-Tagung „View on of Science“)

Vielfalt stärken im naturwissenschaftlich-technischen Sachunterricht – Mehrperspektivische Sichtweisen zur Nutzung sprachlicher und kultureller Heterogenität im Sachunterricht der Grundschule und in der sachunterrichtsdidaktischen Lehrer*innenausbildung - Blumberg, Eva; Brenke, Laurien; Schürmann, Michelle; Gövert, André (Das Projekt "Vielfalt stärken")

Sachunterricht lehren in Zeiten der Pandemie – Eine Online-Befragung zu den Auswirkungen der digitalen Lehre auf den Materialeinsatz in der sachunterrichtsdidaktischen Hochschulausbildung - Thonemann, Lisa; Deutschen, Katrin; Lakemeyer, Jana Marie; Reh, Anne; Blumberg, Eva (GDSU-Journal)

Sachunterricht begründet planen – Das Prozessmodell Generativer Unterrichtsplanung Sachunterricht (GUS) - Tänzer, Sandra; Lauterbach, Roland; Blumberg, Eva; Grittner, Frauke; Lange, Jochen; Schomaker, Claudia (GDSU-Journal)

Potential kernels for radial Dunkl Laplacians - Graczyk, P.; Luks, Tomasz; Sawyer, P. (Canadian Journal of Mathematics)

Effects of the composition of pre-service teacher teams on primary school students’ competencies in (non-)inclusive science lessons. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Digitales Sachunterrichtsstudium in der Corona-Krise – Eine empirische Evaluationsstudie zur Rezeption des Unterstützungsangebots des Paderborner Lernzentrums „Sachunterrichtstreff“ bei Sachunterrichtsstudierenden im Grund- und Förderschullehramt - Deppe, Franziska; Reh, Anne; Blumberg, Eva (GDSU-Journal)

Effects on primary and secondary school students’ academic out-of-school learning experiences in Science Technology Engineering Mathematics (STEM) education. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Schulze, Jan Roland; Crummenerl, Lena Luise; Sicking, Annika; Temmen, Katrin; Blumberg, Eva

Monopolbildung im Zuge der Globalisierung und Digitalisierung der GAFA-Unternehmen (Google, Amazon, Facebook, Apple) - eine wettbewerbspolitische Analyse - Sarsar, Abdelmajid

Kartelle und technischen Absprachen zur Forschung und Entwicklung - Eine wettbewerbspolitische Analyse anhand der Automobilindustrie - Bas, Mikail

Blockchain Technology and the Internet of Thing-Risks and Chances for Supply Chains - Vikue, Baribuma Lucy

Die Fusion von Kaiser's Tengelmann und EDEKA - eine wettbewerbspolitische Analyse - Taskin, Ibrahim

Essen in Kindertageseinrichtungen. Orientierungsmuster von Fachkräften zwischen Anpassung und Ermöglichung - Klein, Alexandra; Landhäußer, Sandra (Soziale Passagen)
Immer mehr Kinder besuchen täglich pädagogische Einrichtungen und verbringen dort zunehmend mehr Zeit; dies führt dazu, dass sie auch vermehrt in pädagogischen Einrichtungen essen. Als Qualitätsmerkmal von Kindertageseinrichtungen wird dabei zunehmend das Thema Essen als gesunde Ernährung zentral. Gleichzeitig liegen bislang erst wenige Studien vor, die auch die Beteiligungs- und Selbstbestimmungsmöglichkeiten von Kindern beim Essen im Alltag der Kindertageseinrichtung betrachten. Auf der empirischen Basis der Frankfurter Kinderbefragung 2018 fragt der vorliegende Beitrag danach, mit welchen kollektiven Orientierungsmustern pädagogische Fachkräfte in Kindertageseinrichtungen die Mahlzeiten gestalten und welche Rolle sie den beteiligten Akteur*innen darin zuweisen. Während in den Gruppendiskussionen einerseits disparate Orientierungen an Ernährungserziehung und Ernährungsbildung sichtbar werden, eint sie andererseits, dass den Kindern selbst kaum substanzielle Einflussmöglichkeiten auf die soziale Gestaltung der Mahlzeit eröffnet werden.
Keywords: Ernährung Mahlzeiten Gruppendiskussion Dokumentarische Methode Beteiligung

Alternative Wahrnehmungen der Welt gelten lassen? Herausforderungen eines rassismuskritischen Unterrichts in der Erzieher_innenausbildung - Kuhn, Melanie; Landhäußer, Sandra (Sozial Extra)
Rassismus kommt als Lerninhalt in den Lehrplänen für die Ausbildung von Erzieher_innen kaum vor. Eine sensible und nicht moralisierende Thematisierung von Rassismus im Unterricht ist so wichtig wie herausfordernd. Die Vermittlung von rassismuskritischem Wissen zum einen und die Selbstpositionierungen der Lehrkräfte zum anderen können dazu beitragen, dass Rassismus nicht unbeabsichtigt bagatellisiert und relativiert wird.
Keywords: Differenz Rassismuskritik Erzieher_innenausbildung Fachschule